Homoeopathic medicine Ruta Graveolens for Pain Management in Musculoskeletal Pain due to Repetitive Strain: A Clinical Case Series (Advancements in Homeopathic Research, 2025)
Repetitive strain caused by repetitive motions and overuse of muscles, tendons, and joints, often leads to pain and dysfunction. This case series demonstrates the effectiveness of homoeopathic medicine Ruta graveolens in managing repetitive strain syndrome in five patients. Five patients aged 35–62 years, all suffering from various forms of repetitive strain injuries—such as medial epicondylitis, lower back strain, and ankle joint pain—were included. Ruta graveolens 30 was prescribed thrice daily for one week, with follow up doses of Ruta graveolens 200 based on clinical response. Pain intensity was monitored using the Visual Analog Scale (VAS) over 4–6 weeks. All patients showed significant reduction in pain scores, with VAS decreasing from 8–9 at baseline to 0–1 within 4–6 weeks of treatment. Symptom relief began within the first week of treatment in all cases. Co-intervention with physiotherapy was provided in all cases. Ruta graveolens demonstrated effectiveness in reducing pain and improving function in patients with repetitive strain syndrome when prescribed on basis of homoeopathic principles.
Keywords: Homoeopathy; Repetitive strain; syndrome; Ruta graveolens